Pengaruh Beberapa Dosis Pupuk Fosfor (P) Terhadap Mutu Benih Berbagai Kultivar Kedelai (Glycine max L. Merril) Selama Pengisian dan Pemasakan Biji - Perdana, Jansen Lea; Rasyad, Aslim; Zuhry, Elza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
An experiment has been designed to investigate the impact of Phosphorous (P) fertilizer on seed quaaliti during seed development of several Soybean (Glycine max L. Merrill) cultivars. The field experiment was carried at University of Riau Agriculture Experiment Station using a complete randomized block design with three replicates. Soybean cultivars such as Willis, Malabar, Kipas Putih and line KM-19-BE were planted in three rates of P fertilizer; ie P0 = 0 kg P2O5 as a control, P1 = 25 kg P2O5, and P2 = 50 kg P2O5 per hektare. Seed quality including seed viability and seed vigor was observed at 10 days interval from 20 to 50 days after anthesis (DAA). It was found that seed quality was very low at early stage of seed development and tent to reach its maximum value as seed matured. Addition of P fertilizer to the plant increased some components of seed quality at early stage of seed development until 40 DAA. The values of seed viability and seed vigor were higher in seed harvested from plant fertilized by P than control, mainly for seed obtained at early seed development. This results indicated that P fertilizer application would improve seed quality especially of seed harvested at early seed development of some soybean cultivars. Keyword : seed viability, seed vigor, seed development, P fertilizer, soybean